Labour Market Progression of Canadian Immigrant Women - Alicia Adsera; Ana Ferrer (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
We use the confidential files of the 1991-2006 Canadian Census, combined with information from O*NET on the skill requirements of jobs, to explore whether Canadian immigrant women behave as secondary workers, remaining marginally attached to the labour market and experiencing little career progression over time. Our results show that the labor market patterns of female immigrants to Canada do not fit the profile of secondary workers, but rather conform to patterns recently exhibited by married native women elsewhere, with rising participation (and wage assimilation). At best, only relatively uneducated immigrant women in unskilled occupations may fit the profile of secondary workers, with slow skill mobility and low-status job-traps. Educated immigrant women, on the other hand, experience skill assimilation over time: a reduction in physical strength and an increase in analytical skills required in their jobs relative to those of natives.
Keywords: J01; J61; F22; 330; skill assimilation; labour market outcomes of immigrant women; wage gaps; female labor force participation; Canadian migration